The interaction between molecular proteins in cancer cells and their role in tumor spread (Journal of the College of Basic Education, 2025)
This research addresses the critical role that molecular protein interactions play in tumor development and progression, beginning with the basic concepts of protein structure and its functions as enzymatic, structural, and signaling agents. It reviews key cellular signaling pathways (MAPK/ERK, PI3K/Akt, TGF‑β/Smad, Wnt/β‑catenin, NF‑κB), and ends with an examination of the interconnection between these pathways and the epithelial–mesenchymal transition (EMT), which grants cancer cells the ability to detach and invade. The literature review highlighted the importance of cancer-associated fibroblasts in remodeling the tumor microenvironment through the secretion of factors such as SDF‑1, IL‑6, and MMPs, thereby contributing to the preparation of a metastatic niche in distant organs. The applied section of the study was based on a sample of forty cancer patients in Kirkuk province, using survey forms and medical records to collect demographic, behavioral, occupational, and environmental data. Statistical descriptive, inferential analysis, and survival modeling were conducted. The findings revealed a significant effect of age, smoking, exposure to oil pollutants, and disease stage in accelerating cancer progression, confirming that the advanced clinical stage is the strongest predictor of poor prognosis.